A atuação do Brasil no conselho de direitos humanos da ONU à luz do princípio da prevalência dos direitos humanos nas relações internacionais - Borges, Caroline Bastos de Paiva (2014)
Brazil is positively acknowledged for their important contributions in the construction of the international rules of promotion and protection of human rights. Participated actively in the process of drafting the Universal Declaration and the Covenants and Conventions major Human Rights. It bears significant international reputation in this field to be considered confident multilateral interlocutor. Moreover, Brazil's foreign policy has become governed since 1988 by an innovative Federal Constitution, which establishes, among others, that the Brazilian international relations must be submitted to the principle of the primacy of human rights, which, by legitimate constitutional power impose themselves on any extra interests would also legitimate. In this context, Brazil joined the Human Rights Council of the UN from its establishment in 2006. This thesis aims to analyze the Brazilian position with the Human Rights Council of the UN, during the period 2006 to 2011, the first two terms of Brazil this multilateral body. The central question is the role of Brazilian foreign policy at the Council is in line with the principle of the primacy of human rights in international relations? Parties and the hypothesis that, despite evident contradictions in the Brazilian position within the Human Rights Council, especially as the votes of Brazil in situations of human rights violations in specific countries, their performance is measured, in part, to the demands of the above principle. In this direction, was structured this thesis into four chapters. In the first chapter, it is to present a historical overview of Brazil's role in the construction of the Global System for protection and promotion of human rights process, and present the main challenges in Brazil to promote the realization internally rights that helped building. In the second chapter, we seek to describe the Human Rights Council of the UN, its features, its institutional setting, its responsibilities and composition as well as its working methods, aiming to contextualize the Brazilian performance. The third chapter presents the constitutional principle of the primacy of human rights in international relations, which serve as a lens from which the role of Brazil in the Council will be analyzed, to then analyze the performance of Brazil in the Council human rights for the duration of their terms (2006-2008 and 2009-2011), especially regarding their participation in votes related to the adoption of new international human rights, the human rights situation in specific countries, the special sessions in periodic review sessions from other countries, as well as Brazilian initiatives in the Council. The methodology used is essentially bibliographic and documentary, based on publications on the subject, as well as the analysis of the minutes of Council meetings in Geneva.